2014
DOI: 10.1088/1054-660x/24/12/125401
|View full text |Cite
|
Sign up to set email alerts
|

Trigonal LaF3: a novel SRS-active crystal

Abstract: Trigonal fluoride LaF 3 , widely known as a host crystal for Ln 3+ -lasants, was found to be an attractive many-phonon Raman material and a subject for the investigation of different χ (3) -nonlinear optical effects. We present the manifestation of photon-phonon interactions related to stimulated Raman scattering (SRS) and Raman-induced four-wave mixing (RFWM) processes, initiated by picosecond exсitation at room temperature. Sesqui-octave-spanning Stokes and anti-Stokes frequency comb generation as well as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…37, In passing, we note that MW-activated CVD also offer routes to forming essentially monoisotopic diamond; a 12 C SCD grown from an isotopically pure 12 CH4/H2 gas mixture, for example, will display significantly higher thermal conductivity than an equivalent diamond containing 12 C and 13 C in natural abundance. 79 Intriguingly, however, many prior studies have shown that adding trace amounts of N2 to the process gas mixture actually enhances the rate of diamond growth from MW-activated CH4/H2 gas mixtures. 49,[80][81][82][83][84][85][86][87][88] The presence of nitrogen in the process gas mixture also affects the surface morphology, encouraging the preferential formation of {100}-faceted surfaces in the case of polycrystalline diamond films (illustrated in Figure 8(d)-(f)) 49,80,89,90 and macroscopic stepbunching (as illustrated in Figure 11) in the case of SCD samples.…”
Section: Effects Of Adding Nitrogen To C/h Containing Gas Mixturesmentioning
confidence: 99%
“…37, In passing, we note that MW-activated CVD also offer routes to forming essentially monoisotopic diamond; a 12 C SCD grown from an isotopically pure 12 CH4/H2 gas mixture, for example, will display significantly higher thermal conductivity than an equivalent diamond containing 12 C and 13 C in natural abundance. 79 Intriguingly, however, many prior studies have shown that adding trace amounts of N2 to the process gas mixture actually enhances the rate of diamond growth from MW-activated CH4/H2 gas mixtures. 49,[80][81][82][83][84][85][86][87][88] The presence of nitrogen in the process gas mixture also affects the surface morphology, encouraging the preferential formation of {100}-faceted surfaces in the case of polycrystalline diamond films (illustrated in Figure 8(d)-(f)) 49,80,89,90 and macroscopic stepbunching (as illustrated in Figure 11) in the case of SCD samples.…”
Section: Effects Of Adding Nitrogen To C/h Containing Gas Mixturesmentioning
confidence: 99%
“…In addition, compounds like LuVO4 and YbVO4 have been found to be promising materials for self-Raman lasers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The refractive indices of BaF 2 and LaF 3 are known as 1.475 and 1.603, respectively . The densities of BaF 2 and LaF 3 crystals are 4.89 and 5.94 g/cm 3 , respectively . Therefore, the electronic polarizability of fluorine in BaF 2 and LaF 3 are obtained as 1.22 and 1.15 Å 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%